Peningkatan Hasil Belajar IPA melalui Model Pembelajaran Iqro’ dengan Berbantuan Media Video pada Siswa Kelas VII A SMP Negeri 2 Amali Kabupaten Bone - Wahyuni, Sri; Citra, Lita (Biology Teaching and Learning, 2019)
Abstract. This research is a classroom action research  that aims to improve the students’ learning outcomes of IPA in class VII A, through the Iqro’ learning model with support of video media in SMP Negeri 2 Amali at Bone regency. Subject of this research consisted of 18 students of class VII A of SMP Negeri 2 Amali consisting of 10 men and 8 women in the second semester of the 2018/2019 academic year. This research was conducted in two cycles with six meetings. The data retrieval of students’ learning outcomes is done in the end of every cycle. Technique of data collection in this research used instrument in the form of a test of learning outcomes in the form of multiple choice consist 25 numbers. The data obtained were analyzed using descriptive statistical analysis. The result of data analysis showed that the average value of students learning outcomes increase from 70,78 in the end of cycle I increase to 85,11 in cycle II. The completeness of students’ learning outcomes in the end of cycle I 61,11% and become 88,89 in cycle II. It can be conclude that the Iqro’ learning model with video media improve the students’ learning outcomes of IPA in class VII A SMP Negeri 2 Amali at Bone regency. Keywords: iqro’ learning model, video media, learning outcomes